2009
DOI: 10.1038/ni.1705
|View full text |Cite|
|
Sign up to set email alerts
|

Cholesterol depletion associated with Leishmania major infection alters macrophage CD40 signalosome composition and effector function

Abstract: CD40, a costimulatory molecule expressed on macrophages, induces expression of interleukin 12 (IL-12) in uninfected macrophages and IL-10 in macrophages infected with Leishmania major. IL-12 suppresses, whereas IL-10 enhances, L. major infection. The mechanisms that regulate this difference in CD40-induced cytokine production remain unclear, but it is known that L. major depletes cholesterol. Here we show that cholesterol influenced the assembly of distinct CD40 signalosomes. Depletion of membrane cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
150
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 55 publications
8
150
1
Order By: Relevance
“…Thus, we concluded that the ERK and p38 signaling pathways are independent of each other. Recent study supports strongly our results by showing the critical role of lipid rafts integrity in p38 and ERK1/2 phosphorylation [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we concluded that the ERK and p38 signaling pathways are independent of each other. Recent study supports strongly our results by showing the critical role of lipid rafts integrity in p38 and ERK1/2 phosphorylation [44].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we concluded that the ERK and p38 signaling pathways are independent of each other. Recent study supports strongly our results by showing the critical role of lipid rafts integrity in p38 and ERK1/2 phosphorylation [44].Previous data indicated that PKC mediate downstream signal following activation through MAP kinase and transcriptional factors. However, this activation of the PKC is involved only in the downstream signaling implicating p38 but not ERK1/2 since their inhibition by the total inhibitor chelerythrine did not affect the phosphorylation of the ERK1/2 kinase.…”
supporting
confidence: 91%
“…CD40 (i.p., 50 mg/mouse; clone 3/23) for 3 d alternatively beginning day 4 postinfection. Disease severity was assessed by measurement of footpad swelling using a digital micrometer (Mitutuyo Japan) and parasite burden (11,12).…”
Section: Mice Parasites and Infectionmentioning
confidence: 99%
“…CD40 is a costimulatory receptor expressed by macrophages, B cells, dendritic cells, and endothelial cells and is the only receptor for which reciprocal signaling has been worked out (10)(11)(12). CD40 stimulation by anti-CD40 Ab results in differential and reciprocal regulation of p38MAPK, ERK1/2 phosphorylation, and IL-10 and IL-12 production (11).…”
mentioning
confidence: 99%
“…Sustained localization of CD40 to lipid rafts has been implicated in the enhanced proliferation of B cells in non-Hodgkin's lymphomas [23]. The manipulation of membrane cholesterol by Leishmania major alters CD40 lipid raft localization and subsequent signaling events, skewing the response from Th1 to Th2 and increasing the susceptibility of macrophages to infection [24]. In addition, CD40 is upregulated and constitutively associates with lipid rafts in an auto-aggressive subset of T cells in a murine model of diabetes [25].…”
mentioning
confidence: 99%